The Analysis of Phase E Students' Problem-Solving Skills on Global Warming Materials with the Help of the Problem-Based Electronic Module - Eldis, Editha Nona; Suban, Maria Enjelina; Riong, Maria Bernadetha Dua (Journal of Innovative Science Education, 2024)
Problem-solving is one of the most essential skills in 21st-century learning which prepares students to face the increasingly complex problems of human life. The phenomenon of global warming remains a big problem that the world is facing. For this reason, students are expected to be able to practice their problem-solving skills in analyzing global warming issues through learning physics. This research aims to determine the extent of students' problem-solving skills related to the global warming phenomenon. The research used a descriptive method with a quantitative approach. This one-shot case study involved 22 phase E students of SMAS Katolik St. Gabriel Maumere. The data collection instrument included 8 question items containing four indicators of problem-solving abilities on global warming. Previously, students had to learn about the topic with the help of a problem-based electronic module. The results showed that the highest level of problem-solving skills was the indicator of implementing strategies with 87%, and the lowest percentage was in the evaluation category with 64%. The overall score of problem-solving skills was 72.25% in the high category, meaning that the application of the problem-based e-module provides positive results for students to transfer their knowledge in analyzing problems that occur in real life.